2021
DOI: 10.3390/app11146409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Training Program on Hepatic Fat Content and Cardiometabolic Risk in Postmenopausal Women: The Randomized Controlled Trial

Abstract: This 10-week randomized controlled trial investigates the effects of two different training modalities on hepatic fat content and cardiometabolic risk in sedentary postmenopausal women. Besides, alterations in physical fitness, hepatic fat content, and cardiometabolic risk will be associated with changes in those blood parameters that are usually modifiable by exercise training. Postmenopausal women (N = 32; ~61 years) were randomly assigned to one of the following treatment groups; (1) based on international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 107 publications
1
9
0
Order By: Relevance
“…These discrepancies might stem from differences in participant characteristics, such as gender, weight status, the duration and intensity of WB-EMS training, dietary habits, and other factors [42]. Our findings align with the hypothesis that combined electrical stimulation training enhances lipid oxidation, emphasizing triglycerides as a primary energy source for such training [41].…”
Section: Cardiometabolic Markerssupporting
confidence: 76%
See 1 more Smart Citation
“…These discrepancies might stem from differences in participant characteristics, such as gender, weight status, the duration and intensity of WB-EMS training, dietary habits, and other factors [42]. Our findings align with the hypothesis that combined electrical stimulation training enhances lipid oxidation, emphasizing triglycerides as a primary energy source for such training [41].…”
Section: Cardiometabolic Markerssupporting
confidence: 76%
“…A similar study by Reljic, Konturek, Herrmann, Neurath, and Zopf [33] found a noteworthy reduction in triglycerides following a 12-week WB-EMS program among obese women. In another study, a 10-week WB-EMS intervention showed positive effects on the lipid profiles of healthy sedentary women [41]. In contrast, Park, Na, Choi, Seon, and Do [18] reported no significant improvement in lipid profiles after a 6-week WB-EMS regimen in young women.…”
Section: Cardiometabolic Markersmentioning
confidence: 93%
“…There is no relationship between the perceived benefits and the gender of the participants. Between genders, statistically significant differences were only found in the perceived benefit of "Prevent myocardial infarction", with a higher proportion in men than in women [20].…”
Section: Discussionmentioning
confidence: 91%
“…Clinical trials with WB-EMS show benefits in the reduction of low back pain by improving quality of life [13,14], obesity treatment [15,16], osteoporosis and osteopenia [17,18], diabetics [19] and patients with cardio-metabolic risk [20]. Athletes have also benefited from the use of this technology, improving their performance [21][22][23] as well as the general population seeking to improve their well-being and body composition [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes related to rhabdomyolysis were determined by several studies. Changes of creatine-kinase, myoglobin and other markers of muscle damage were reported by eight of the included studies (6,7,13,14,19,20,22,24). Two trials (19,30) reported significant post-intervention CK raises.…”
Section: Diseases Of the Musculoskeletal Systemmentioning
confidence: 99%